2004
DOI: 10.1111/j.1541-4337.2004.tb00060.x
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Review of Campylobacter and Poultry Processing

Abstract: Campylobacter has been recognized as a leading bacterial cause of human gastroenteritis in the United States, with 40000 documented cases annually. Epidemiological data suggest that contaminated products of animal origin, especially poultry, contribute significantly to campylobacteriosis. Thus, reduction of contamination of raw poultry would have a large impact in reducing incidence of illness. Contamination occurs both on the farm and in poultry slaughter plants. Routine procedures on the farm such as feed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
175
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(185 citation statements)
references
References 143 publications
4
175
0
6
Order By: Relevance
“…Epidemiological data suggest that contaminated products of animal origin, especially poultry, contribute significantly to foodborne diseases. Reduction of raw poultry contamination levels would thus have a large impact on reducing the incidence of illness (Keener et al 2004).…”
mentioning
confidence: 99%
“…Epidemiological data suggest that contaminated products of animal origin, especially poultry, contribute significantly to foodborne diseases. Reduction of raw poultry contamination levels would thus have a large impact on reducing the incidence of illness (Keener et al 2004).…”
mentioning
confidence: 99%
“…Thus, the contaminated samples analyzed herein are a public health concern. Keener et al (2004) have reported that the Food and Drug Administration (FDA) and United States Department of Agriculture (USDA) approved the irradiation of poultry meat at a maximum dose of 3.0 kGy to control causative pathogens of foodborne illness, such as Campylobacter sp. No microbiological standard regarding the presence of Campylobacter sp.…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, bird-to-bird transmission within flocks is very rapid and it was demonstrated that once a broiler flock becomes infected with Campylobacter, close to 100% of birds are reported to become colonized in a very short time Newell & Fearnley, 2003). Moreover it is known that, after in vivo-passage, organisms can exhibit an enhancement of colonization potential of at least 1,000-fold in most strains and up to 10,000-fold in some strains (Berndtson et al, 1992;Keener et al, 2004). The most important Campylobacter species associated with human infections are C. jejuni, C. coli, C. lari and C. upsaliensis (European Food Safety Authority, 2011;Friedman et al, 2000;Robinson, 1981).…”
Section: The Diseasesmentioning
confidence: 99%
“…Chemical treatments include washing of carcasses in electrolyzed or chlorinated water, dipping carcasses in a solution containing acidified sodium chlorite before chilling, immersion in acetic or lactic acid or in sodium triphosphate solutions. Physical treatments include freezing of contaminated carcasses, heat-treatment of fresh broiler carcasses, dipping of fresh carcasses in hot water immediately before chilling, radiation, exposure to dry heat, and ultrasonic energy in combination with heat (Corry & Atabay, 2001;Keener et al, 2004). In spite of the effort that has been done to control these pathogens, they are still a major cause of foodborne diseases (European Food Safety Authority, 2011;Nyachuba, 2010) (Figure 1).…”
Section: Antibiotic Resistancementioning
confidence: 99%